Chemo-immunoablation of solid tumors: A new concept in tumor ablation - Meng, Liangliang; Wei, Yingtian; Xiao, Yueyong (Frontiers in Immunology, 2023)
Chemical ablation was designed to inject chemical agents directly into solid tumors to kill cells and is currently only used clinically for the palliative treatment of tumors not for physical ablation or unresectable tumors. The application and combination of different drugs, from anhydrous ethanol, and glacial acetic acid to epi-amycin, have been clinically tested for a long time, and the effectiveness is not satisfactory due to the poor diffusion and concentration of chemical agents. Immunotherapy is considered a prospective oncologic therapeutic. Still, the clinical applications were limited by the low response rate of patients to immune drugs and the immune-related adverse effects caused by high doses. The advent of intratumoral immunotherapy has well addressed these issues. However, the efficacy of intratumoral immunotherapy alone is uncertain, as suggested by the results of preclinical and clinical studies. In this study, we will focus on the research of improving immunosuppressive tumor microenvironment with chemoablation and intratumoral immunotherapy, the synergistic effect between chemotherapeutic drugs and immunotherapy, and propose a new concept of intratumoral chemo-immunoablation, which opens a new perspective for tumor treatment from direct killing of tumor cells while, enhancing systemic anti-tumor immune response, and greatly reducing adverse effects of drugs.